Ionic liquid cations as methylation agent for extremely weak chalcogenido metalate nucleophiles. Issue 20 (15th May 2019) - Peters, Bertram; Santner, Silke; Donsbach, Carsten; Vöpel, Pascal; Smarsly, Bernd; Dehnen, Stefanie
Abstract : Imidazolium-based ionic liquids served to selectively methylate terminal chalcogenide ligands of chalcogenidometalate clusters [Sn10 S16 O4 (SMe)4 ] 4−, [Mn4 Sn4 Se13 (SeMe)4 ] 6−, and [Hg6 Te10 (TeMe)2 ] 6− . Abstract : Selective in situ methylation of terminal chalcogenide ligands of molecular chalcogenido metalate anions in ionothermal reactions with alkylimidazolium-based ionic liquids yields a series of organo-functionalized chalcogenido metalate compounds. We present the syntheses and crystal structures of (C4 C1 C1 Im)4+ x [Sn10 S16 O4 (SMe)4 ][An] x (1a–1f ), (dmmpH)6 [Mn4 Sn4 Se13 (SeMe)4 ] (2 ), and (C n C1 Im)6 [Hg6 Te10 (TeMe)2 ] (3a, 3b ). The methylation was confirmed by Raman spectroscopy, and the optical absorption properties of the methylated compounds were determined and compared to purely inorganic analogs.